2020
DOI: 10.3389/fimmu.2020.01071
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of S100A9 and S100A12 Expression in Monocyte-Macrophage System in Hyperglycemic Conditions

Abstract: code on the respective gene promoters in M1 macrophages. Mechanistically, this regulation relies on action of histone methyltransferases SMYD3 and SET7/9. The results define an important role for epigenetic regulation in macrophage mediated inflammation in diabetic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 101 publications
2
38
0
Order By: Relevance
“…Moreover, hyperglycemia was found to induce production of pro-inflammatory cytokines and S100 proteins in human primary macrophages [234][235][236]. One of major pro-inflammatory cytokines is IL-1beta that has a complex role in tumors and promotes tumorigenesis, tumor invasiveness and immunosuppression [237,238].…”
Section: The Key Metabolic Features Of M1 Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, hyperglycemia was found to induce production of pro-inflammatory cytokines and S100 proteins in human primary macrophages [234][235][236]. One of major pro-inflammatory cytokines is IL-1beta that has a complex role in tumors and promotes tumorigenesis, tumor invasiveness and immunosuppression [237,238].…”
Section: The Key Metabolic Features Of M1 Macrophagesmentioning
confidence: 99%
“…S100A9 and S100A12 that are induced by high glucose in primary human macrophages have multiple cellular targets and link inflammatory processes in cancer [239]. We have recently demonstrated that hyperglycemia induces activating histone code on the promoters of these genes in primary human macrophages, that shows that there is a link between glycolytic metabolism and the epigenetic level of regulation in macrophages [236]. However, it remains to be understood how these processes interact in TAMs.…”
Section: The Key Metabolic Features Of M1 Macrophagesmentioning
confidence: 99%
“…An upcoming upliftment is immediately required for a proper systematic understanding of the differences in predispositions of genetics among different populations, that undergoes patho-physiological mechanisms. Hence, a foremost Table 1 Antidiabetic drugs for COVID-19 diabetic complication (Honce and Schultz-Cherry 2019;Almond et al 2020;Dixon and Peters 2020;Wan et al 2020;Hoffmann et al 2020;Li et al 2017;Spiegel et al 1983;Zhu et al 2020) informative and knowledgeable research in this relationship and in its management must be warranted. All over the world, in more than 200 countries or territories, there exists greater than 14,650,000 confirmed cases, with more than 600,000 deaths.…”
Section: Future Prospects and Conclusionmentioning
confidence: 99%
“…Focusing on human macrophages, a distinct study reported that hyperglycemia increased the expression of S100A8 and S100A9 in macrophages and that expression of another S100/calgranulin, S100A12 (or EN-RAGE, a ligand of the receptor for advanced glycation end products [RAGE]) [ 35 ], was sustained in human macrophages after glucose levels were returned to euglycemia [ 36 •]. Mechanistically, it was found that hyperglycemia increased the acetylation of histones which were bound to the S100A9 and S100A12 promoters in the “M1” or pro-inflammatory macrophages in processes involving SMYD3 and SET7/9 [ 36 •].…”
Section: Epigenetics: Long-lasting Memory and Consequences To The Cardiovascular Systemmentioning
confidence: 99%